Stress-Dependent Scaling Behavior of Ferroelectric Hysteresis Loop in 0-3 PZT-Cement Composites - N. Jaitanong (2018)
© 2015 Taylor & Francis Group, LLC. PZT-cement based composites are developed for use as sensors for smart concrete structures. However, these sensors would in real life be under a certain stress. PZT -cement composites were produced using 50% PZT vol. content. The ferroelectric (P-E) hysteresis behaviors and the effect of stress on the P-E hysteresis of the composites were reported. A noticeable reduction in Pi r was observed, while Ei c remained approximately the same when the stress was increased. Finally, the scaling law between the hysteresis loop area < A > and the field frequency f, field amplitude E 0 and applied compressive stress σwere shown to follow the relation.